Transpassive-repassivation process of Ni-base superalloys : The role of hidden subsurface alloy layer - Yue, Xiaoqi; Larsson, Alfred ; 0000-0002-8932-8381; Chen, Dihao; Grespi, Andrea ; 0000-0003-3132-4318; Abbondanza, Giuseppe; Lienert, Ulrich; Hegedüs, Zoltan; Jeromin, Arno; Keller, Thomas F.; Scardamaglia, Mattia; Shavorskiy, Andrey; Dong, Chaofang; et al. (Corrosion Science, 2025)
Passivity refers to spontaneous formation of a passive film on the surface of metals. High stability of the passive film on advanced alloys relies on the repassivation ability of the alloys in corrosive environments. Two Ni-base superalloys (Ni-22Cr-9Mo-5Fe-2Nb and Ni-18Cr-3Mo-20Fe-5Nb) are studied to elucidate the mechanism of repassivation through a combination of multimodal in-situ synchrotron X-ray measurements, electrochemical measurements, and first principles calculations. The synchrotron X-ray analyses enabled in-situ probing of the passive film and the hidden subsurface alloy layer. The results reveal chemical and structural evolutions of both the passive film and the underlying subsurface alloy layer under transpassive condition. The first principles calculations demonstrate a crucial role of the subsurface alloy layer in the repassivation of the alloys. Upon passivity breakdown at high electrochemical potentials, the passive film rich in Cr oxide becomes highly defective with vacancies, and metal dissolution leads to generation of vacancies (mainly Ni) in the subsurface alloy layer. This promotes repassivation process by enhanced outward Cr diffusion strengthening the metal bond (more Cr-Ni bonds) in the subsurface alloy layer and, together with the enrichment of high valence Mo- and Nb-oxides in the passive film, lead to repassivation when the high potential is removed, which is different from Fe-rich alloys.
Publisher Copyright: © 2025 The Authors
Keywords: Ni-base superalloy; Passive film; Repassivation; Subsurface alloy layer; Synchrotron X-ray measurement, DFT calculation